Audiovisual Translation of Slang Words and Phrases and Their Types of Equivalence in 50/50 Movie - Rahmawati Rahmawati (Passage, 2015)
The study aims to identify the types of slang, subtitling strategies applied, and the types of equivalence discovered in the movie subtitle. There are three different theoretical frameworks employed in this study in order to analyze the data, those are the classification of types of slang based on the lexical meaning proposed by Finnegan et al. (1992) and the word-formation process proposed by Yule (1996), the subtitling strategies as proposed by Gottlieb (1992 in Ghaemi and Benyamin, 2010); and the types of equivalence by Kade (1968 in Pym, 2010). Descriptive Qualitative approach was employed as the research design in this study. There are 370 slang words and phrases as the collected data which were taken from 50/50 movie subtitle. The result revealed that out of 12 classifications of types of slang, there were 8 types identified, and Synonymy (55.14%) was the most frequent type of slang applied in the movie subtitle. Similar to the types of slang, there are 7 out of 10 subtitling strategies applied in the movie subtitle, and the most-used strategy applied in the movie subtitle was Transfer (43.43%). Furthermore, in types of equivalence, there are 3 out of 4 types with the most frequent type applied in the movie subtitle was One to Several equivalence (95.9%). In addition, in the combination of three analyses, Synonymy-Transfer-One to Several equivalence was mostly appeared simultaneously in the movie subtitle which has 73 occurrences. Therefore, it can be concluded that types of slang, subtitling strategies, and types of equivalence are correlated to each other. It happened because the subtitling strategies as the strategies which were used to translate the slang words and phrases resulted in the translated version of the slang that were classified into types of equivalence. Keywords: Slang words and phrases, Types of Slang, Subtitling Strategies, and Types of Equivalence.